The Role of the Ombudsman in Public Service Institutions - Nufaris Elisa (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The role of the Ombudsman within local government is very important. Based on Law Number 37 of 2008 concerning the Ombudsman, the Ombudsman’s function is mandated to supervise the implementation of public services in Indonesia. The role of the Ombudsman is crucial in improving public services, which are still relatively low; therefore, it is necessary to analyze the Ombudsman’s role in Public Service Institutions and its implications for the realization of good governance in public services. This study uses field research conducted directly in the field with a non-doctrinal or socio-legal approach. The data sources consist of primary and secondary data, including legal materials (primary, secondary, tertiary). Data collection methods were carried out through interviews and documentation, which were then presented in a descriptive-analytical manner. The Ombudsman’s roles that have been implemented include assessing the compliance of public service providers, which is a rapid review by the Ombudsman as an effort to prevent maladministration. In addition, investigations based on public reports are also conducted. The implications of supervision by the Ombudsman have resulted in the realization of good governance principles, namely public participation, effectiveness, efficiency, transparency, professionalism, and competence in public services.